2017
DOI: 10.1039/c7dt02469j
|View full text |Cite
|
Sign up to set email alerts
|

Mono-BHT heteroleptic magnesium complexes: synthesis, molecular structure and catalytic behavior in the ring-opening polymerization of cyclic esters

Abstract: Numerous heteroleptic 2,6-di-tert-butyl-4-methylphenolate (BHT) magnesium complexes have been synthesized by treatment of (BHT)MgBu(THF) with various alcohols. Molecular structures of the complexes have been determined by X-ray diffraction. The magnesium coordination number in [(BHT)Mg(μ-OBn)(THF)] (3) and [(BHT)Mg(μ-O-tert-BuCH)(THF)] (4) is equal to 4. Complexes formed from esters of glycolic and lactic acids, [(BHT)Mg(μ-OCHCOOEt)(THF)] (5) and [(BHT)Mg(μ-OCH(CH)COOCHCOOBu)(THF)] (6) contain chelate fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 95 publications
8
76
1
Order By: Relevance
“…Benzyl alcohol (BnOH, 99%, Acros Organics, Geel, Belgium) and tert-butyl alcohol ( t BuOH, 99%, Merck, NJ, USA) were distilled over BaO and stored under argon. 2-Chloro-2-oxo-1,3,2-dioxaphospholane [45], 2-tert-butoxy-2-oxo-1,3,2-dioxaphospholane t BuOEP [23], and BHT-Mg catalyst [(BНТ)Mg(µ-OBn)(THF)] 2 [46] were prepared according to previously described methods (for details, see Section S1 in the Supporting Information).…”
Section: General Experimental Remarksmentioning
confidence: 99%
“…Benzyl alcohol (BnOH, 99%, Acros Organics, Geel, Belgium) and tert-butyl alcohol ( t BuOH, 99%, Merck, NJ, USA) were distilled over BaO and stored under argon. 2-Chloro-2-oxo-1,3,2-dioxaphospholane [45], 2-tert-butoxy-2-oxo-1,3,2-dioxaphospholane t BuOEP [23], and BHT-Mg catalyst [(BНТ)Mg(µ-OBn)(THF)] 2 [46] were prepared according to previously described methods (for details, see Section S1 in the Supporting Information).…”
Section: General Experimental Remarksmentioning
confidence: 99%
“…Two bridging benzyloxide ligands connect the two Mg atoms, forming a nearly flat Mg 2 O 2 rhomboid core ( Fig. 2a), analogous to those observed in [(BHT)Mg(OBn)(THF)] 2 (Nifant'ev et al, 2017) Trinuclear complex (II) is located on a twofold crystallographic axis (Z 0 = 0.5) ( Fig. 3)…”
Section: Resultsmentioning
confidence: 64%
“…For example, the complexes (BHT) 2 Mg(THF) 2 (Calabrese et al, 1988; THF is tetrahydrofuran), n BuMg(BHT)(THF) 2 and [(-EtO)Mg-(BHT)(THF)] 2 (Nifant'ev et al, 2016), activated with alcohols, have demonstrated high efficiency in the ROP of lactide, "-caprolactone and !-pentadecalactone (Nifant'ev et al, 2016;Wilson et al, 2014Wilson et al, , 2015Fang et al, 2012;Chen et al, 2012). Using [(-RO)Mg(BHT)(THF)] 2 [R = Et or benzyl (Bn)] as examples, it has been demonstrated that activation with an alcohol is not necessary if both phenoxy and alkoxy groups are present within the same Mg complex (Nifant'ev et al, 2016(Nifant'ev et al, , 2017. Therefore, new heteroleptic (ArO)Mg(OAlkyl) complexes are of interest.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations